Perhitungan Perbandingan Tonase Bauksit Menggunakan Data Truck Count, dan Tonase Hasil Analisa Laboratorium di Bauxite Processing Plant 1 dan 2 PT. Jaga Usaha Sandai - Site sandai, Sandai Kiri, Kecamatan Sandai, Kabupaten Ketapang, Kalimantan Barat - Rahul Hutmi; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2022)
Abstract. The volume and tonnage of stockwash at the Bauxite Processing Plant have a great influence on the achievement of the company's production targets, so it is necessary to carry out good monitoring so that the loss of material in the stockwash can be minimized. Material loss can occur in the process, transportation and washing as well as the process of stacking material in the stockwash. Material that has been stacked on the stockwash can also be one of the factors for the occurrence of material loss, another factor is the uncertainty of the material production calculation data that has been washed in the field. So to ensure its production for that it is necessary to carry out laboratory analysis. Based on the calculation results that have been carried out, the difference between stock balance CF 50% and stock balance from laboratory analysis at Bauxite Processing Plant 1 and 2 is 3.389,05 tons. Based on the comparison chart, the results of the stock balance calculation from the laboratory analysis look more accurate when compared to the calculation of stock balance data truck count CF 50%. Keywords : Bauksit, Tonase, Lose material.